Immunogenicity of SARS-CoV-2 Trimeric Spike Protein Associated to Poly(I:C) Plus Alum - dos-Santos, Júlio Souza; Firmino-Cruz, Luan; da Fonseca-Martins, Alessandra Marcia; Oliveira-Maciel, Diogo; Perez, Gustavo Guadagnini; Roncaglia-Pereira, Victor A.; Dumard, Carlos H.; Guedes-da-Silva, Francisca H.; Santos, Ana C. Vicente; Leandro, Monique dos Santos; Ferreira, Jesuino Rafael Machado; Guimarães-Pinto, Kamila; et al. (Frontiers in Immunology, 2022)
The SARS-CoV-2 pandemic has had a social and economic impact worldwide, and vaccination is an efficient strategy for diminishing those damages. New adjuvant formulations are required for the high vaccine demands, especially adjuvant formulations that induce a Th1 phenotype. Herein we assess a vaccination strategy using a combination of Alum and polyinosinic:polycytidylic acid (Poly(I:C)) adjuvants plus the SARS-CoV-2 spike protein in a prefusion trimeric conformation by an intradermal (ID) route. We found high levels of IgG anti-spike antibodies in the serum by enzyme linked immunosorbent assay (ELISA) and high neutralizing titers against SARS-CoV-2 in vitro by neutralization assay, after one or two boosts. By evaluating the production of IgG subtypes, as expected, we found that formulations containing Poly(I:C) induced IgG2a whereas Alum did not. The combination of these two adjuvants induced high levels of both IgG1 and IgG2a. In addition, cellular immune responses of CD4+ and CD8+ T cells producing interferon-gamma were equivalent, demonstrating that the Alum + Poly(I:C) combination supported a Th1 profile. Based on the high neutralizing titers, we evaluated B cells in the germinal centers, which are specific for receptor-binding domain (RBD) and spike, and observed that more positive B cells were induced upon the Alum + Poly(I:C) combination. Moreover, these B cells produced antibodies against both RBD and non-RBD sites. We also studied the impact of this vaccination preparation (spike protein with Alum + Poly(I:C)) in the lungs of mice challenged with inactivated SARS-CoV-2 virus. We found a production of IgG, but not IgA, and a reduction in neutrophil recruitment in the bronchoalveolar lavage fluid (BALF) of mice, suggesting that our immunization scheme reduced lung inflammation. Altogether, our data suggest that Alum and Poly(I:C) together is a possible adjuvant combination for vaccines against SARS-CoV-2 by the intradermal route.